2020
DOI: 10.35316/alifmatika.2020.v2i2.199-211
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hubungan Antara Kecerdasan Logis Matematis Dengan Kemampuan Komunikasi Matematis Siswa

Abstract: This study examined the relationship of logical intelligence students' mathematical communication skills. This research was conducted at the senior high school of Jenggawah at the even semester of the 2019/2020 academic year. The population in this study were all of the high school students of class X IPA, the total students were 144 students in the 2019/2020 academic year. The sampling technique of this study was using 64 Randoms Cluster Sampling as well as the instruments used in the form of mathematical log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The result shows that students who have good logical ability will have good communication skills as well (Nisa, Mukhlis, & Maswar, 2020). The students who are able to solve problems, are able to find the reason the problems and will also be able to communicate them (Nisa, Mukhlis, & Maswar, 2020). This is in line with the research conducted by Irawan, Suharta, and Suparta (2016), which presents the higher logical-mathematical intelligence possessed by students.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The result shows that students who have good logical ability will have good communication skills as well (Nisa, Mukhlis, & Maswar, 2020). The students who are able to solve problems, are able to find the reason the problems and will also be able to communicate them (Nisa, Mukhlis, & Maswar, 2020). This is in line with the research conducted by Irawan, Suharta, and Suparta (2016), which presents the higher logical-mathematical intelligence possessed by students.…”
Section: Introductionsupporting
confidence: 76%
“…This is indicated by the significant difference between the mathematics learning outcomes of students who memorize the Qur'an and the students who do not memorize the Qur'an. The research conducted by Nisa, Mukhlis, and Maswar (2020) also shows a significant correlation between logical-mathematical ability and high school students' communication skills. The result shows that students who have good logical ability will have good communication skills as well (Nisa, Mukhlis, & Maswar, 2020).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous research has shown a positive relationship between logical intelligence and mathematical literacy abilities. Students who have high logical thinking abilities tend to find it easy to understand and solve mathematical problems, while students who have moderate and low logical thinking abilities tend to experience difficulty and difficulty understanding and solving mathematical problems (Nisa et al, 2020). However, intelligence logical it's not the only one factor Which influence ability literacy mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical logical intelligence is a form of student skills in counting and using logic (Widyawati & Rahayu, 2020;Ayuningsih & Ciptahadi, 2020). This intelligence is closely related to students' skills in solving mathematical problems, namely being able to think and formulate solutions in a logical order (Nisa, Mukhlis & Maswar, 2020;Pradestya, Imswatama & Balkist, 2020;Hitalessy, Mataheru & Ayal, 2020). However, students' skills in solving math problems are still very low, where students are very weak in solving non-routine questions, especially contextual so that this research provides concrete examples to students contextually.…”
Section: Introductionmentioning
confidence: 99%